Library consortium: IITA, Ibadan, Nigeria experience (2012)
Purpose – This paper aims to describe the library consortium experienced at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. Activities involved improving researchers’ timely access to resources for research for development. Design/methodology/approach – The approach taken was a librarian interview and observation of library records. Findings – The consortium involves agricultural libraries in both developing and developed countries. Using the library software Inmagic database enhances the web-based centralized online public access catalogue of all the participating institutions, the CGV Library. This enabled access to their comprehensive collections, promoting better library services to agricultural researchers. Hence, it bridges the digital gap between developing and developed countries. They are involved in joint acquisition of electronic journals and timely response to sharing their independent collections through electronic document delivery services. Practical implications – The paper recommends that Nigerian libraries, especially agricultural research institutes, could emulate the IITA library consortium. Originality/value – The paper provides recommendations to libraries wishing to form consortia in Nigeria and notes the positive impacts that this would have on national development.